PEMBERDAYAAN MASYARAKAT DESA MELALUI EKOWISATA AIR TERJUN SALOSIN DI DESA SUKAHURIP - Garvera, R Rindu; Sihabudin, Aan Anwar; Taufiq, Otong Husni (Galuh International Journal of Community Service and Development, 2024)
Sukahurip village people are familiar with ecotourism programs which are based on community empowerment. The village has an eco-tourism waterfall called Salosin that offers a view of the beauty of the mountains and the village people’s hospitality in general. Salosin Waterfall has a beautiful ecosystem and the many trees make the area closely related to the green mountains. However, the lack of empowerment of the surrounding community in utilizing the beauty of Salosin Waterfall natural tourism is an important problem. This is the goal of efforts to achieve community welfare to achieve the ideals of development priorities in the economic sector for the surrounding community. The method of implementing activities in the form of assistance to the community in developing the potential around Salosin Waterfall economic potential so that people can get economic income. What happens in Salosin Waterfall ecotourism is the development and management of the tour. In contrast, the understanding of other potentials that can benefit from ecotourism for improving community welfare seems less touched so it requires encouragement and support for community empowerment so that it can increasingly have a positive impact on the people of Sukahurip Village.